Implementation of HPV tests in Latin America: what we learned; what should we have learned, and what can we do better? - Godoy, Luani Rezende (2022)
Cervical cancer is caused by HPV. Although it is the fourth most common type of cancer diagnosed and the fourth cause of cancer death, cervical cancer is nearly completely preventable because of the vaccination and screening available. The present review aims to map the initiatives conducted to implement or evaluate the implementation of HPV testing in Latin American countries. We performed the review by searching on PubMed in the English language and on grey literature, as most of the information about the guidelines used was found in governmental websites in the Spanish language. We only found information in eight countries concerning HPV testing as primary screening. Only Mexico has established HPV-based screening in all territories. There are three countries with regional implementation. Two countries with pilot studies indicated results that supported implementation. Finally, there are another two countries with a national recommendation. We have learned that HPV implementation is feasible and a very promising tool for reducing cervical cancer morbidity and mortality. The costs associated with saving lives and reducing suffering due to morbidity of a preventable disease must be pragmatically evaluated by the Latin America governments, and improving outcomes must be a mandatory priority for those that are responsible for addressing an organized system of cervical cancer screening.